PERKEMBANGAN KUALITAS GURU DAN TENAGA KEPENDIDIKAN DI SEKOLAH DASAR - Izzati, Norlaili; Ahmad Rifky Maulana; Abdul Bashith (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is an integral process in developing the character, cognitive abilities, and physical aspects of students in harmony with their social and natural environment. As the main pillar in the development of quality and characterful human resources, education requires an effective and quality system. The level of progress of a nation's education is greatly influenced by the quality of educators, especially teachers, who have professional competence. In Indonesia, the low quality of teachers is still a major challenge and raises public doubts about the quality of national education. Therefore, improving the quality of teachers is an important agenda in efforts to reform education. Teachers as professional workers must facilitate themselves with a set of experiences, skills, and knowledge about teaching, in addition to having to master the substance of the science they are studying. However, in reality there are still many teachers who have not carried out their duties according to expectations. This paper aims,to examine the development of teacher competence, the challenges faced in the world of education, and strategies for improving the quality of teachers and education personnel. The discussion is carried out by referring to various related literature and policies, in order to show the relationship between teacher professionalism and improving the quality of education as a whole.